2016
DOI: 10.1021/acs.langmuir.6b02360
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Interaction of Pluronics L61 and L64 with a DOPC Lipid Bilayer: An Atomistic Molecular Dynamics Study

Abstract: ABSTRACT:We investigate the interactions of Pluronics L61 and L64 with a dioleylphosphatidylcholine (DOPC) lipid bilayer by atomistic molecular dynamics simulations using the all-atom OPLS force field. Our results show that the initial configuration of the polymer with respect to the bilayer determines its final conformation within the bilayer. When the polymer is initially placed at the lipid/water interface, we observe partial insertion of the polymer in a U-shaped conformation. On the other hand, when the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Antiseptic Picloxydine, Octenidine, Miramistin [470], Polyhexamethylene Biguanide [471] Insecticide Parathione [132], Fipronil [472], Dibutyl succinate [203] Former Drugs d-sotalol, cisapride [473], piracetam (status varies among countries) [474], ORG-12962 [199] Toxic xenobiotic Polybrominated-diphenyl-ethers [475], Bisphenol [476], Perfluoroalkyls [477], nitroaromatic explosives (TNT,2A, and 24DA) [478][479][480][481], 1,4-Dioxane [482], Benzo[a]pyrene [483] Nanomaterials Graphene [484][485][486][487], Carbon Dots [488], Phosphorene Oxide Nanosheets [489], Gold Nanoparticles [490][491][492], Titanium Dioxide Nanoparticles [493], Generic Nanoparticles (coarse grained) [494], Fullerene [495][496][497][498], Previous reviews [499] Polymers Poly(ethyleneoxide)-Poly-(propylene oxide) [500], polyethylenimine [501], Poloxamer [502,503], Pluronics [504,505], poly(ethyleneglycol)-desferrioxamine/ gallium [506], PEG functionalized with carbochydrates [507] and peptides…”
Section: Application Xenobioticmentioning
confidence: 99%
“…Antiseptic Picloxydine, Octenidine, Miramistin [470], Polyhexamethylene Biguanide [471] Insecticide Parathione [132], Fipronil [472], Dibutyl succinate [203] Former Drugs d-sotalol, cisapride [473], piracetam (status varies among countries) [474], ORG-12962 [199] Toxic xenobiotic Polybrominated-diphenyl-ethers [475], Bisphenol [476], Perfluoroalkyls [477], nitroaromatic explosives (TNT,2A, and 24DA) [478][479][480][481], 1,4-Dioxane [482], Benzo[a]pyrene [483] Nanomaterials Graphene [484][485][486][487], Carbon Dots [488], Phosphorene Oxide Nanosheets [489], Gold Nanoparticles [490][491][492], Titanium Dioxide Nanoparticles [493], Generic Nanoparticles (coarse grained) [494], Fullerene [495][496][497][498], Previous reviews [499] Polymers Poly(ethyleneoxide)-Poly-(propylene oxide) [500], polyethylenimine [501], Poloxamer [502,503], Pluronics [504,505], poly(ethyleneglycol)-desferrioxamine/ gallium [506], PEG functionalized with carbochydrates [507] and peptides…”
Section: Application Xenobioticmentioning
confidence: 99%
“…The polymer molecular weight, its microstructure, and, more complicated to rationalize, the procedure followed for the self-assembly seem to be all variables affecting the final stability of the vesicles. , Specifically, for amphiphilic copolymers, the hydrophobic/hydrophilic ratio and the molar mass of the polymers seem to be the main factors affecting both the cellular uptake and the change in the membrane properties . Because of the difficulty in gaining an atomistically resolved picture of the vesicles’ structure, molecular simulations have been extensively used to investigate the effects that polymers, surfactants, or small molecules have on the structure of lipid bilayers. …”
Section: Introductionmentioning
confidence: 99%
“…However, their use is limited by solubility and stability, which make them difficult to use alone . Studies have shown that mixed micelles of polymers with different HLBs are more stable in aqueous solutions . Therefore, we speculate that the mixed use of two pairs of pluronics would complement each other and that the formation of a combination of binary mixed micelles would have greater thermodynamic stability.…”
Section: Introductionmentioning
confidence: 93%